(untitled) (Annals of Medical Research, 2021)
Aim: Chronic spontaneous urticaria (CSU) is characterized by recurrent urticaria, angioedema and a combination of both over a period of more than 6 weeks. Anti-immunoglobulin E (IgE) monoclonal antibody (omalizumab) treatment is an effective and safe treatment modality that can be applied in antihistamine-resistant cases in patients with CSU and the urticaria control test is a simple and useful test that evaluates the control level of the disease over the past 4 weeks.Material and Methods: Following appropriate urticaria control tests, 82 test results of 41 patients with CSU (23 females, 18 males) who received subcutaneous anti-IgE treatment at a dose of 300 mg/4 weeks for 6 months were evaluated retrospectively.Results: With each question, there was a statistically significant difference between the mean scores before treatment and at 6 months of treatment (p: 0.001 for question 1, p: 0.001 for question 2, p: 0.001 for question 3, p: 0.001 for question 4). As a result, 95.1% of the patients included in the study achieved a complete and/or partial response to treatment.Conclusion: Omalizumab treatment in patients with chronic spontaneous urticaria (CSU), is an effective and safe treatment modality, independent of the patients’ serum IgE levels, eosinophil counts, thyroid-stimulating hormone levels, C-reactive protein and sedimentation rates, presence or absence of anti-nuclear antibody (ANA) and regardless of whether angioedema is associated with chronic spontaneous urticaria. Furthermore, the urticaria control test is a practical test that can be used to evaluate the efficiency of treatment in CSU patients